2017
DOI: 10.1371/journal.pone.0174260
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous induction of Graves’ hyperthyroidism and Graves’ ophthalmopathy by TSHR genetic immunization in BALB/c mice

Abstract: BackgroundGraves’ disease is the most common form of autoimmune thyroid disorder, characterized by hyperthyroidism due to circulating autoantibodies. To address the pathological features and establish a therapeutic approach of this disease, an animal model carrying the phenotype of Graves’ disease (GD) in concert with Graves’ Ophthalmopathy (GO) will be very important. However, there are no ideal animal models that are currently available. The aim of the present study is to establish an animal model of GD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The method of TSHR genetic immunization and vivo electroporation was also widely used [7,8,17]. A study recently reported that over 80% of immunization mice have developed to GD and the incidence of goiter was more than 90% with immunization and electroporation [18]. However, this approach may be at risk of causing death in mice after the last immunization [7,15].…”
Section: Discussionmentioning
confidence: 99%
“…The method of TSHR genetic immunization and vivo electroporation was also widely used [7,8,17]. A study recently reported that over 80% of immunization mice have developed to GD and the incidence of goiter was more than 90% with immunization and electroporation [18]. However, this approach may be at risk of causing death in mice after the last immunization [7,15].…”
Section: Discussionmentioning
confidence: 99%
“…They rationalize the absence of inflammatory infiltrates in their latest study as consistent with a “hit and run” immune-mediated inflammatory event 30 . Another research group, also employing intramuscular DNA immunization followed by electroporation, found that a large fraction of their animals developed elevated thyroxine levels, anti-TSHR antibodies, and goiters 31 . Extraocular muscle and adipose tissue volumes were increased.…”
Section: Thyroid-stimulating Hormone Receptor Immunization In Rodent mentioning
confidence: 99%
“…Key pathological features of TED include extraocular muscle or orbital fat expansion and soft tissue inflammation due to increased adipose tissue, oedema, and glycosaminoglycan (GAG) production in orbital tissue. 1 Left untreated, TED can cause photophobia, diplopia, pain, exposure keratopathy and proptosis. Compressive optic neuropathy threatening vision, however, is the feared complication.…”
Section: Introductionmentioning
confidence: 99%
“…Compressive optic neuropathy threatening vision, however, is the feared complication. 1 Current therapeutic options include discontinuation of smoking, correction of any thyroid abnormalities, administration of non-steroidal or steroidal antiinflammatory drugs, orbital low dose radiation therapy or surgery (e.g., orbital decompression).…”
Section: Introductionmentioning
confidence: 99%